Microbial Model Halobacterium salinarum in Screening of Synthetic Analogues of Antibiotic Turbomycin A with Anticancer Activity - A. S. Trenin; E. A. Tsvigun; O. P. Bychkova; S. N. Lavrenov (Антибиотики и Химиотерапия, 2020)
The microbial test-system based on cultivation of Halobacterium salinarum developed earlier for screening inhibitors of sterol biosynthesis and proposed for screening anticancer antibiotics, proved to be efficient in revealing anticancer compounds among derivatives of tris(1-alkylindol-3-yl)methylium, synthetic analogues of antibiotic turbomycin A. Most of the methane sulfonate and chloride salts of such compounds, investigated with the help of the H.salinarum test-system, showed no activity (MIC>32 mcM), while several derivatives, containing N-butyl or N-pentyl substituents were rather active against the bacterial strain. The MICs of them against H.salinarum were 8 mcM for total and 1 mcM for partial inhibition of the bacterial growth. The results of the study correlated with the results of other investigations that revealed anticancer activity of such compounds in tumor cell cultures. Therefore, the H.salinarum test-system demonstrated its availability for screening compounds with anticancer activity.